iReserve: An Online Event Reservation for Lipa City Cultural with SMS Notification - Mayling Capuno; Jerome Benigno; Russel Reyes; Kielly Chrizza Mae Tojino (Philippine Association of Institutions for Research, Inc., 2021)
The study proposed a web-based research iReserve: An Online Event Reservation for Lipa City Cultural, to integrate SMS Notification. In the existing manual system of reservation, the major challenge on the administration was conflicts of schedule with the event reservation. Thus, iReserve: An Online Event Reservation for Lipa City Cultural was proposed to serve as a useful tool for booking events and send updated notifications about the status of the request event details by integrating SMS technology. iReserve is designed to process the booking request and search for clients' available target event schedules from the system database. The study used the software development life cycle in developing the proposed application. The web application structure was designed using workflow, entity-relationship, context, and use case diagrams. The web application was developed using different open sources such as HTML, CSS, JavaScript, PHP, and MySQL. iReserve was evaluated using ISO 9126 software evaluation tool assessing the web applications' functionality, reliability, usability, efficiency, portability, and maintainability. The study concluded that using several diagrams and a combination of open source technologies, the web application designed and developed would meet the specified functionalities.